THE ADAPTATION OF TEACHERS AND STUDENTS TOWARD DIGITAL LEARNING AT SMA NEGERI 1 SUSUKAN AMID TECHNOLOGICAL LIMITATIONS - Muhammad Arief Wijayanto; Nawal; Putri Diah Ayu Nurul Khamidah; Achmad Maimun (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2026)
This study explores how teachers and students at SMA Negeri 1 Susukan adjust to digital learning while dealing with limited technological resources. The research was conducted using a descriptive qualitative approach with classroom observation and interviews to obtain comprehensive information about teachers' and students' adaptation strategies, obstacles, and perceptions. The results show that teachers have adopted digital media such as projectors, PowerPoint, instructional video materials, and Google Forms, although the implementation is inconsistent because of unavailable devices, unstable internet connections, and limited facilities. Furthermore, students also respond positively to digital lessons, even though they face similar challenges of limited internet access, personal devices, and confusion when teachers do not provide detailed explanations. These findings confirm the Diffusion of Innovation and Community of Inquiry theories that adaptation has been implemented, but it has not been optimized due to the lack of infrastructure support and teaching presence. Therefore, this study is important to provide an empirical description about the challenges of digital adaptation in schools with limited technology and serve as a reference for developing programs to improve technology infrastructure and strengthen teachers' and students' digital competencies.